Emily Dickinson’s Poetry in Ukrainian and Russian Translation: Synaesthetic Shift - Shurma, Svitlana; Chesnokova, Anna (Vertimo studijos, 2017)
[full article, abstract in English; abstract in Lithuanian]This paper focuses on synaesthetic shift occurring in translation of Emily Dickinson’s poetry into Ukrainian and Russian. The research is in line with Redka’s (2009) view of verbal and poetic synaesthesia, a trope which is structurally represented as a word combination, a sentence or even a poem, and manifests itself in the text as the author’s perception of objective reality via visual, colour, tactile, olfactory, auditory and gustatory sensation. We aim to describe two types of poetic synaesthesia: metaphoric, which is realized in the text as an image and is represented in cognition as conceptual metaphor or metonymy; and non-metaphoric, which is triggered by a combination of verbal images and phonetic instrumentation and versification. We thus hypothesise that synaesthetic shift between source and target images leads to the change of the original image and results from changes in versification and phonetic instrumentation patterns in poetry, verbal images and conceptual cross-domain mapping.
Keywords: none